La Pensée technocritique de Gaston Bardet - Antoine Perron (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The architect and urban planner Gaston Bardet (1907-1989) is probably one of the most original and prolific French urban theorists of the twentieth century. After being marginalized in the 1950s and 1960s, his work has been the subject of several articles and scientific papers since the late 1970s. Although we are now well acquainted with the main themes and ideas structuring Bardet’s theories, his reflection on techniques does not seem to have been studied yet. This article aims to explore the “technocriticism” developed by Bardet, highlighting its main ideological roots, its implications for architecture and its genuinely ecological dimension. Between radicality and irrationality, Gaston Bardet’s “dark green” ecology might provide a better understanding of certain dead-ends in our struggle against global disruption.